Identification of High-Yielding Iron-Biofortified Open-Pollinated Varieties of Pearl Millet in West Africa - Gangashetty, Prakash I.; Riyazaddin, Mohammed; Sanogo, Moussa Daouda; Inousa, Drabo; Issoufou, Kassari Ango; Asungre, Peter A.; Sy, Ousmane; Govindaraj, Mahalingam; Ignatius, Angarawai Ijantiku (Frontiers in Plant Science, 2021)
Pearl millet is a predominant food and fodder crop in West Africa. This study was carried out to test the newly developed open-pollinated varieties (OPVs) for field performance and stability for grain yield, grain iron (Fe), and grain zinc (Zn) contents across 10 locations in West Africa (i.e., Niger, Nigeria, Mali, Burkina Faso, Senegal, and Ghana). The test material consisted of 30 OPVs, of which 8 are Fe/Zn biofortified. The experiment was conducted in a randomized complete block design in three replications. ANOVA revealed highly significant variability for grain yield and micronutrient traits. The presence of genotype × environment (G × E) indicated that the expressions of traits are significantly influenced by both genetic and G × E factors, for grain Fe and Zn contents. Days to 50% flowering and plant height showed less G × E, suggesting these traits are largely under genetic control. The genotypes CHAKTI (46 days), ICTP 8203 (46 days), ICMV 177002 (50 days), ICMV 177003 (48 days), and Moro (53 days) had exhibited early flowering across locations leading to early physiological maturity. CHAKTI (1.42 t/ha yield; 62.24 mg/kg of grain Fe, 47.29 mg/kg of grain Zn) and ICMP 177002 (1.19 t/ha yield, 62.62 mg/kg of grain Fe, 46.62 mg/kg of grain Zn) have performed well for grain yield and also for micronutrients, across locations, compared with the check. Additive Main Effect and Multiplicative Interaction (AMMI) ANOVA revealed the highly significant genotypic differences, the mean sum of squares of environment, and its interaction with the genotypes. Based on the AMMI stability value (ASV), the most stable genotype is SOSAT-C88 (ASV = 0.04) for grain yield and resistance to downy mildew; mean grain yield and stability rankings (YSI) revealed that the genotypes CHAKTI, SOSAT-C88, and ICMV IS 99001 were high yielding and expressed stability across regions. The strong correlation (r = 0.98∗∗) of grain Fe and Zn contents that merits Fe-based selection is highly rewarding. CHAKTI outperformed over other genotypes for grain yield (71% higher), especially with early maturing varieties in West Africa, such as GB 8735, LCIC 9702, and Jirani, and for grain Fe (16.11% higher) and Zn (7% higher) contents across locations, and made a candidate of high-iron variety to be promoted for combating the micronutrient malnutrition in West and Central Africa (WCA).